Pelemahan Masyarakat Sipil dan Gagalnya Desain Kelembagaan Demokrasi Pasca Reformasi 1998 - Damianus Benediktus Gene Djo Djo; Patrisius Eduardus Kurniawan Jenila (Journal of Politics and Policy, 2022)
The fall of Suharto did not make the position of civil society grow and had a significant impact on the trajectory of the consolidation of Indonesian democracy after the 1998 Reformation. Instead, in the sharing of the results, the picture is of a civil society that is much weaker and unable to support democratic agendas. The weakening of civil society after the 1998 reform was motivated by many factors, such as the tragedy of the 1965 massacre and the strengthening of the position of oligarchic groups in the post-1998 reform democratic system. Oligarchic networks are able to hijack democratic institutions through democratic means for the accumulation and protection of material resources. The operationalization of oligarchic networks in weakening the position of civil society manifests itself in repressive measures in a number of regulations that restrict the expression of freedom in the public sphere, such as the Law on Electronic Information and Transactions, which has so far often been usedas an instrument by public officials in silencing critics.In the midst of weakening and subordinating the position of civil society, it increasingly confirms that the institutional approach—an approach that is often used to measure the quality of democracy—is not enough to support the sustainability of an empowered and bargaining civil society in powerrelations. This is exactly where structural approaches come into play to address the impasse of democracy and the sustainability of civil society in post-1998 democratic politics. Through the use of qualitative approaches with descriptive analysis methods, this paper sees that the democratic agendas after the 1998 reform have not changed much towards improvement due to the weakening of the position of civil society.